2023
DOI: 10.3389/fsurg.2023.1125665
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anterior and posterior approaches in Treating odontoid fractures: a meta-analysis and systematic review

Abstract: BackgroundOdontoid fractures account for 15%–20% of cervical injuries. Although the operation methods vary in different types, the superiority of overall outcomes of the anterior approach (AA) and posterior approach (PA) in treating odontoid fractures still remains controversial. Thus, a meta-analysis was performed comparing AA and PA for these fractures.MethodsThe relevant studies were searched in PubMed/MEDLINE, Cochrane Library, EMBASE, China Biological Medicine (CBM), and Wanfang Database from the onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“… 24) There are conflicting meta-analyses, comparing the clinical outcomes of the anterior and posterior approaches to odontoid fractures. 4 31) Lvov et al 17) showed that anterior odontoid screw fixation had a lower rate of fusion and a higher rate of reoperation with no difference in technical failure or mortality. Bao et al 4) reported that the anterior approach had a shorter operative time and greater motion retention with no difference in complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 24) There are conflicting meta-analyses, comparing the clinical outcomes of the anterior and posterior approaches to odontoid fractures. 4 31) Lvov et al 17) showed that anterior odontoid screw fixation had a lower rate of fusion and a higher rate of reoperation with no difference in technical failure or mortality. Bao et al 4) reported that the anterior approach had a shorter operative time and greater motion retention with no difference in complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 4 31) Lvov et al 17) showed that anterior odontoid screw fixation had a lower rate of fusion and a higher rate of reoperation with no difference in technical failure or mortality. Bao et al 4) reported that the anterior approach had a shorter operative time and greater motion retention with no difference in complications and mortality. The fusion rate, rather than the mechanical complication rate, was primarily used to evaluate the outcome of the surgical treatment of odontoid fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation